Genre as Implicit Methodology in a Collaborative Writing Initiative - Lazar, Gillian; Ellis, Eddie (International Journal of English Studies, 2011)
It is often assumed that the academic genres taught by EAP specialists at universities are fixed and stable, provide easily accessible exemplars for student writers and feature in programmes running prior or parallel to the students‟ courses. This paper describes a collaborative writing initiative in which these assumptions were challenged. A writing specialist collaborated with a team of academics on a Post-graduate Certificate of Education (PGCE) in order to improve students‟ writing of a Masters-level assignment. While the writing specialist was implicitly committed to a genre-based teaching methodology, this was necessarily framed in terms of the aims of the PGCE academics, who were particularly concerned about improving student understanding of both assignment guidelines and assessment criteria. An impact study detailing positive outcomes for this collaboration, suggests that a genre-aware pedagogy can still inform a programme for writing within the disciplines even when the focus on genre is implicit.